PD-L2 act as an independent immune checkpoint in colorectal cancer beyond PD-L1 - Zhu, Lvyun; Qu, Ying; Yang, Junru; Shao, Tong; Kuang, Jingyu; Liu, Chuanyang; Qi, Yanhua; Li, Ming; Li, Yingying; Zhang, Sujuan; Wang, Jingyang; Liu, Yu; et al. (Frontiers in Immunology, 2024)
IntroductionImmunotherapy, especially immune checkpoint blockade (ICB), holds promise as a therapeutic strategy in colorectal cancer (CRC) by harnessing the patient’s immune system to target malignant cells. Particularly, the PD-1/PD-L1 axis is widely recognized for its critical role in tumor microenvironment immunosuppression. Antibodies targeting PD-1 or PD-L1 have shown sustained efficacy against various cancers, including CRC. Nonetheless, many CRC patients exhibit limited responses to such immunotherapy, and the resistance mechanisms remain incompletely understood.MethodsWe conducted experiments with C57BL/6 mice, and used the MC38 cell line for ICB treatment studies in syngeneic mouse models. Gene and protein analyses were performed using qPCR, Western Blot, and flow cytometry, with bioinformatics for clinical data survival analysis.ResultsIn this study, we reveal that targeting PD-L2 emerges as a complementary therapeutic strategy to PD-1/PD-L1 blockade in CRC. Although PD-L2 is also inducible by IFNγ, like PD-L1, it displays a unique spatial distribution within the tumor microenvironment, implying discrete roles in immune evasion. Additionally, we uncovered a significant correlation between PD-L1 and PD-L2 expression levels and the infiltration of various immune cells, encompassing multiple dendritic cell (DC) subtypes. This correlation implies an enhanced antigen presentation process that may be unleashed by blocking these two immune checkpoints.DiscussionOur results highlight the significance of PD-L2 as an essential immune checkpoint alongside PD-L1 and emphasize its potential as a target for bolstering antitumor immunity in colorectal cancer.